Enactment of the Tatweer education policy in Saudi Arabia: a comprehensive analysis - Allohibi, Omar (2025)
This study explores the enactment of the Tatweer Education Policy (TEP) in four schools in Saudi Arabia. It focuses on the perspectives of teachers and leaders on how the policy has impacted their practice. The study scrutinises how the TEP is implemented, specifically in four schools in Medinah selected to participate in the Tatweer program. The data was collected using a qualitative case study design, with the specific methods being online interviews and document reviews. The study's findings reveal that even though the TEP facilitates collaborative approaches, self-evaluation systems, and learner-centred teaching strategies, teachers and school leaders face significant challenges during implementation. One of the leading challenges relates to the dual nature of supervision, where the local education offices are responsible for providing resources, support, monitoring and supervision to all government schools and emphasise a more traditional and outdated system of education. On the other hand, there is the Tatweer Units (TUs) responsible for supporting Tatweer schools and providing them with the capability to follow the TEP system by assisting them in building and evaluating plans, raising awareness in relation to the TEP activities, and training teachers based on the guidelines of the policy, and advocates for more contemporary child-centred methods. The findings show that this conflict results in confusion, which hinders the implementation of the TEP. The findings also highlighted other factors impeding the implementation of the TEP, including heavy workloads, insufficient time, lack of resources, and slow bureaucratic decisions. Based on the conclusions drawn, the study recommends that there needs to be better coherence in supervision, schools should receive the support required by the TEP, the local needs of schools should be considered by involving all stakeholders in the policy development process and schools should be allowed to play a greater role in decision-making. This will ensure that the TEP and reforms it calls for can be realised in alignment with Saudi Arabia's Vision 2030 and the realisation of its benefits.